MONITORING OF SALMONELLA ENTERICA RESISTANCE TO ANTIBIOTICS AMONG CHILDREN WITH ACUTE INTESTINAL INFECTIONS - Lusta, Maksym; Voronkova, Olga; Chornyi, Valerii; Breus, Artem; Yesaulenko, Inna; Shulzhenko, Dmytro; Maistrenko, Yevhen; Ponomarova-Herasymiuk, Tetiana (Eastern Ukrainian Medical Journal, 2024)
Introduction. Uncontrolled and unjustified prescribing of antibacterial drugs in the treatment of various infections, in particular, COVID-19, and their use in veterinary medicine and food industry were the predictors of antibacterial resistance development of both opportunistic and pathogenic bacteria. Salmonella enterica is a major public health problem, causing 155,000 to 300,000 deaths per year in developing countries. Non-typhoidal Salmonella enterica are common etiological agents of acute intestinal infections in children. The purpose of the study was to establish the prevalence of Salmonella enterica and its serovars, the sensitivity level of selected strains to antibacterial drugs among children with suspected acute intestinal infection for the period from 2021 to 2023. Materials and Methods. For the period from 2021 to 2023, 3,340 stool samples of children suspected of having an acute intestinal infection, who were undergoing inpatient treatment in the infectious department for children of the Municipal Non-Commercial Enterprise «City Clinical Hospital No. 6» of the Dnipro City Council, were examined. Stool specimens were cultured on nutrient media, suspicious colonies were identified by the classic bacteriological method and automated method using the VITEK 2 compact 15 bacteriological analyzer. Salmonella enterica serotype and the sensitivity of the selected strains to antibacterial drugs were determined in accordance with the recommendations of the European Committee on Antimicrobial Susceptibility Testing. Research Results. During the period from 2021 to 2023, 3,340 bacteriological studies of stool samples of children with suspected acute intestinal infection were conducted, 143 strains of Salmonella enterica were isolated (seeding rate 4.2 %) (p-value <0.005). It was established that the highest isolation rate from the stools of children with suspected acute intestinal infection with non-typhoidal Salmonella enterica was observed in the period from May to September. Among Salmonella enterica serovars, 67.8 % of strains were Salmonella enterica subsp. enterica serovar Enteritidis, 24.5 % – Salmonella enterica subsp. enterica serovar Typhimurium. The number of ampicillin-susceptible strains of Salmonella enterica increased by 30 % between 2021 and 2023. The number of Salmonella enterica strains sensitive to amoxicillin-clavulanic acid increased by 13.4 % between 2021 and 2023. The rate of sensitivity of Salmonella enterica strains to the 3rd generation cephalosporins remained high and was more than 97 %. A decrease in the sensitivity of Salmonella enterica strains to pefloxacin and ciprofloxacin was revealed, which indicated a tendency to acquire resistance genes to fluoroquinolone drugs. Conclusion. Among pathogenic microorganisms, Salmonella enterica causes acute intestinal infection in children in 4.2 % of cases. β‑lactam antibiotics may be the drugs of choice for the treatment of acute intestinal infections in children caused by Salmonella enterica.